Intracerebral Hemorrhage in a Young Urban Population: Etiologies and Outcomes in Patients 50 and Younger Presenting in the Department of Neurology, Jinnah Postgraduate Medical Centre - Devi, Lata; Sher, Khalid; Ahmad, Rizwana Malahat; Farooq, Maheen; Abrar, Ateeba; Nisha, . (Biological and Clinical Sciences Research Journal, 2025)
Intracerebral hemorrhage (ICH) in young adults is a significant neurological emergency associated with considerable morbidity and mortality. Understanding its etiological profile and prognosis is essential for timely management and prevention. Objective: To determine the etiologic profile and prognosis of intracerebral hemorrhage (ICH) in patients aged 18–50 years presenting to the Neurology Department at Jinnah Postgraduate Medical Centre (JPMC), Karachi, Pakistan. Methods: A cross-sectional study was conducted at Ward 28, Department of Neurology, JPMC Karachi, from December 7, 2024 to March 7, 2025, after obtaining ethical approval. One hundred twenty-nine patients aged 18–50 years with confirmed ICH (within 24 hours of onset) were enrolled using non-probability consecutive sampling. Demographic and clinical data, including comorbidities such as hypertension, diabetes mellitus, hyperlipidemia, cerebral amyloid angiopathy (CAA), and anticoagulant use, were recorded. Patient outcomes were assessed at hospital discharge. Results: The mean systolic blood pressure was 143.6 ± 21.5 mmHg. Hypertension was the most prevalent comorbidity, present in 64 patients (50%), followed by hyperlipidemia in 39 (30%), diabetes mellitus in 25 (19%), anticoagulant use in 19 (15%), and cerebral amyloid angiopathy in 13 (10%). Out of the total, 104 patients (81%) were discharged successfully, while 25 (19%) died during hospitalization. Conclusion: Intracerebral hemorrhage in young adults is associated with high morbidity and mortality, with hypertension being the most common underlying risk factor. These findings highlight the need for aggressive risk factor management in younger populations to reduce the burden of ICH.